Epidural Interlay Graft for Pituitary Surgery: A 4-Year Institutional Experience - Snyder, Rita; Lee, Sungho; Athukuri, Prazwal; Ngo, Emmeline Monique Tan; Fox, Meha Goyal; Fakhri, Samer; Takashima, Masayoshi; Force, Bahar Kapoor; Samson, Susan Leanne; Gallagher, Kathleen Kelly; Yoshor, Daniel; Jalali, Ali (Journal of Neurological Surgery Part B: Skull Base, 2023)
Objective Sellar repair techniques with varying complexity and effectiveness have been employed to reduce the incidence of postoperative cerebrospinal fluid (CSF) leaks following endoscopic transsphenoidal pituitary surgery. This study describes our institutional experience with a minimalistic, highly effective approach to sellar repair.Methods The authors performed a retrospective review of consecutive cases of transsphenoidal pituitary surgery performed at our institution. All included subjects underwent sellar repair with an epidural interlay graft. Relationships between patient and tumor characteristics, incidence of CSF leak, adjunct repair techniques, and endocrine outcomes were examined.Results Three hundred and thirty-four (334) cases were included. Intraoperative CSF leak was encountered in 116 cases (34.7%), and postoperative CSF leak occurred only once (0.3%) early in the series. Seventy intraoperative CSF leaks were successfully repaired with an epidural interlay alone, including 13 high-flow leaks. Our rate of fat graft use (1.2%), nasoseptal flap (3.0%), and lumbar drain placement (6.6%) in the second half of the series showed a significant decline compared with the first half, indicating increased reliance on the interlay graft over time. Our 65% functional macroadenoma remission rate compares favorably with large historical series.Conclusion Simple sellar repair using an epidural interlay graft is highly effective in preventing postoperative CSF leaks, including cases of high-flow intraoperative leaks. More complex repair techniques are reserved for select high-risk cases or those with inadequate sellar bony ledges. With this technique, there has been no postoperative CSF leak at our institution in over 300 consecutive transsphenoidal pituitary surgeries.
Keywords: endoscopic transsphenoidal; pituitary adenoma; pituitary surgery; sellar repair; cerebrospinal fluid leak; nasoseptal flap